KARAKTERISTIK PENDERITA ENDOMETRIOSIS DAN ADENOMIOSIS DI RSUP DR. M. DJAMIL PADANG PERIODE JANUARI 2017 – OKTOBER 2018 - Hidayat, Arde; Hendry, Dedy (Andalas Obstetrics And Gynecology Journal, 2019)
Background : Endometriosis is a benign gynecological disorder characterized by the presence of endometrial glands and stroma outside the normal location. Endometriosis is a chronic disorder which is a major cause of infertility, dysmenorrhea, dyspareunia and chronic pelvic pain with varying degrees of pain. Management of endometriosis can be in the form of medical therapy and/ or surgical therapy. Surgical therapy can be conservative and definitive.Objective : This study aims to obtain the characteristics of patients with endometriosis and adenomiosis who are operated at Dr. M. Djamil Padang for the period of January 2017 - October 2018.Method : This was descriptive retrospective study, using medical records data of endometriosis patient at Dr. RSUP M. Djamil Padang.Result : The results of the study obtained 160 cases of endometriosis patients who were operated during that period but only 154 patients had complete data in the medical record. Endometriosis cases were common among age of 36-45 years old (42.2%), married (87.7%), nullipara (61.7%), ovarian endometrioma (44.8%),laparotomy method (54.6%), type of surgery was cystectomy (44.8%), and pain reduced post operation (62.7%).Conclusion : Most frequent characteristics of endometriosis patient were operated in the 36-45 year age group, married, nullipara, ovarian endometrioma, laparotomy method, type of surgery was cystectomy and pain reduced post operationKeywords: endometriosis, adenomiosis, dysmenorrhea